Method for manufacturing slurry, method for manufacturing composite resin material, and composite resin material

JP2026166734APending Publication Date: 2026-10-14ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059881
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、機械的強度に優れ、かつ、体積抵抗率が低い複合樹脂材料を得ることが可能なスラリーの製造方法を提供することができる。 また、本発明によれば、機械的強度に優れ、かつ、体積抵抗率が低い複合樹脂材料を得ることが可能な複合樹脂材料の製造方法を提供することができる。 さらに、本発明によれば、機械的強度に優れ、かつ、体積抵抗率が低い複合樹脂材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166734000001
    Figure 2026166734000001
  • Figure 2026166734000002
    Figure 2026166734000002
Patent Text Reader

Abstract

The present invention provides a method for producing a slurry that can yield a composite resin material with excellent mechanical strength and low volume resistivity. [Solution] The slurry production method of the present invention includes the step of mixing a dispersion A, which is obtained by dispersing fluororesin particles in a dispersion medium A, and a dispersion B, which is obtained by dispersing carbon nanotubes in a dispersion medium B, to obtain a slurry, wherein the dispersion medium A and the dispersion medium B are nonpolar solvents.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for producing a slurry, a method for producing a composite resin material, and a composite resin material. [Background technology]

[0002] Fibrous carbon nanostructures, such as carbon nanotubes (hereinafter sometimes referred to as "CNTs"), are being explored for a wide range of applications due to their excellent conductivity, thermal conductivity, sliding properties, and mechanical properties. Therefore, in recent years, development has been underway to create composite resin materials that combine the excellent properties of fibrous carbon nanostructures with those of resin materials, such as processability and strength, and the properties of fibrous carbon nanostructures, such as conductivity, by utilizing the superior properties of fibrous carbon nanostructures.

[0003] Specifically, for example, Patent Document 1 discloses a method for producing a slurry that substantially does not use surfactants, comprising a mixing step of mixing fluororesin particles having a volume average particle diameter of 5 μm or more and 250 μm or less, fibrous carbon nanostructures, and a dispersion medium all at once to obtain a mixed liquid, and a dispersion step of dispersing the mixed liquid using a wet jet mill, as well as a method for producing a composite resin material using the slurry. Furthermore, Patent Document 1 states that a slurry and a composite resin material can be obtained that substantially does not contain surfactants and has excellent dispersibility of fibrous carbon nanostructures. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2017-31323 [Overview of the project] [Problems that the invention aims to solve]

[0005] In recent years, composite resin materials containing fluororesins and carbon nanotubes have been required to have excellent mechanical strength and low volume resistivity. However, the slurry manufacturing method and composite resin material manufacturing method described in Patent Document 1 had room for improvement in obtaining a composite resin material having high mechanical strength and low volume resistivity.

[0006] Therefore, the present invention aims to provide a method for producing a slurry that can yield a composite resin material with excellent mechanical strength and low volume resistivity. Furthermore, the present invention aims to provide a method for producing a composite resin material that has excellent mechanical strength and low volume resistivity. Furthermore, the present invention aims to provide a composite resin material that has excellent mechanical strength and low volume resistivity. [Means for solving the problem]

[0007] The inventors diligently conducted research to achieve the above objectives. As a result, the inventors discovered that when obtaining a slurry for preparing a composite resin material containing fluororesin and carbon nanotubes, instead of mixing the fluororesin and carbon nanotubes together, mixing a dispersion of fluororesin particles in a nonpolar solvent with a dispersion of carbon nanotubes in a nonpolar solvent to form a slurry can increase the mechanical strength of the composite resin material obtained using the slurry while reducing its volume resistivity. This discovery led to the completion of the present invention.

[0008] In other words, the present invention aims to advantageously solve the above problems, and the present invention is a method for producing a slurry, comprising the steps of [1] mixing a dispersion A obtained by dispersing fluororesin particles in a dispersion medium A and a dispersion B obtained by dispersing carbon nanotubes in a dispersion medium B to obtain a slurry, wherein the dispersion medium A and the dispersion medium B are nonpolar solvents. In this way, by mixing a dispersion of fluororesin particles and a dispersion of carbon nanotubes to make a slurry, and by using nonpolar solvents as dispersion mediums for both dispersions, it is possible to increase the mechanical strength of the resulting composite resin material while reducing its volume resistivity.

[0009] [2] Preferably, the method for producing the slurry further includes the steps of: dispersing the fluororesin particles in the dispersion medium A to prepare the dispersion A; and dispersing the carbon nanotubes in the dispersion medium B to prepare the dispersion B.

[0010] [3] In the slurry manufacturing method described above, it is preferable that the fluororesin particles are dispersed using a rotor-stator type disperser in the step of preparing the dispersion A. By dispersing the fluororesin particles using a rotor-stator type disperser in this way, aggregates of the fluororesin particles can be eliminated, and the uniformity in compounding with carbon nanotubes can be increased, thereby improving the conductivity of the resulting composite resin material.

[0011] [4] In the method for producing the slurry described above, it is preferable that the dispersion medium A and the dispersion medium B are the same nonpolar solvent. By using the same nonpolar solvent in this way, the conductivity of the resulting composite resin material can be increased without impairing the mechanical strength of the resulting composite resin material.

[0012] [5] In the method for producing the slurry described above, it is preferable that dispersion A and dispersion B are substantially free of dispersants. By substantially free of dispersants in dispersions A and B, the generation of gases in the resulting composite resin material can be suppressed. In this invention, "substantially free of dispersants" in the dispersion means that no dispersants other than those inevitably present as impurities are added. For example, the content of dispersants relative to the total solid content in the dispersion is less than 0.01% by mass, preferably zero.

[0013] [6] In the method for producing the slurry described above, it is preferable that the volume-average particle diameter of the fluororesin particles in the dispersion A is 100 μm or less. Thus, if the volume-average particle diameter of the fluororesin particles in the dispersion A is less than or equal to the above upper limit, the uniformity in composite formation with carbon nanotubes is increased, and the conductivity of the resulting composite resin material can be improved. Furthermore, clogging of the fluororesin particles can be suppressed, thereby improving the productivity of the slurry. In this invention, the "volume-average particle diameter" of the fluororesin particles can be measured by the method described in the examples.

[0014] [7] In the method for producing the slurry described above, the content of carbon nanotubes in the slurry is preferably 0.01% by mass or more and 0.5% by mass or less with respect to the total solid content in the slurry. Thus, if the content of carbon nanotubes in the slurry is above the lower limit, the conductivity of the resulting composite resin material can be increased. On the other hand, if the content of carbon nanotubes in the slurry is below the upper limit, the conductivity of the resulting composite resin material can be increased without impairing the mechanical strength of the resulting composite resin material.

[0015] [8] In the method for producing the slurry described above, it is preferable that the dispersion A and the dispersion B are mixed using a stirrer equipped with a stirring unit and a motor. By mixing the dispersion A and the dispersion B using a stirrer equipped with a stirring unit and a motor in this way, the fluororesin particles and carbon nanotubes can be uniformly composited, and the conductivity can be increased without impairing the mechanical strength of the resulting composite resin material.

[0016] [9] In the above method for producing a slurry, it is preferable that the dispersion medium A and the dispersion medium B are each independently at least one selected from the group consisting of cyclohexane, hexane, pentane, cyclopentane, heptane, and octane. In this way, when the dispersion medium A and the dispersion medium B are set to the predetermined dispersion media, the fluororesin particles and the carbon nanotubes can be uniformly composited, and the electrical conductivity can be enhanced without impairing the mechanical strength of the obtained composite resin material.

[0017] Further, the present invention aims to advantageously solve the above problems, and the present invention is

[10] a method for producing a composite resin material, which comprises a step of producing a slurry by the above method for producing a slurry, and a step of removing the dispersion medium from the slurry. According to the above method for producing a composite resin material, a composite resin material having excellent mechanical strength and reduced volume resistivity can be produced.

[0018] Further, the present invention aims to advantageously solve the above problems, and the present invention is

[11] a composite resin material produced by the above method for producing a composite resin material. As described above, the composite resin material produced by the aforementioned method for producing a composite resin material has excellent mechanical strength and low volume resistivity.

Effects of the Invention

[0019] According to the present invention, it is possible to provide a method for producing a slurry that makes it possible to obtain a composite resin material having excellent mechanical strength and low volume resistivity. Further, according to the present invention, it is possible to provide a method for producing a composite resin material that makes it possible to obtain a composite resin material having excellent mechanical strength and low volume resistivity. Furthermore, according to the present invention, it is possible to provide a composite resin material having excellent mechanical strength and low volume resistivity.

Modes for Carrying Out the Invention

[0020] Hereinafter, embodiments of the present invention will be described in detail. Herein, the slurry manufacturing method of the present invention can be suitably used, for example, in the manufacturing method of the composite resin material of the present invention. Furthermore, the composite resin material of the present invention can be suitably used in the manufacture of the composite resin material of the present invention, and the composite resin material of the present invention is manufactured by the composite resin material manufacturing method of the present invention and can be suitably used, for example, in the manufacture of semiconductor manufacturing equipment parts, chemical tanks, wafer cleaning containers, cleaning nozzles, antistatic sheets, integrated circuit trays, wafer carriers, chemical hoses, pipe fittings, diaphragms, and sealing materials.

[0021] (Method for manufacturing slurry) The slurry production method of the present invention includes a step of mixing a dispersion A, which is obtained by dispersing fluororesin particles in dispersion medium A, and a dispersion B, which is obtained by dispersing carbon nanotubes in dispersion medium B, to obtain a slurry (mixing step), and may optionally include other steps. Furthermore, the slurry production method of the present invention is characterized in that both dispersion medium A and dispersion medium B are nonpolar solvents. Furthermore, according to the slurry manufacturing method of the present invention, it is possible to manufacture a slurry capable of forming a composite resin material that has excellent mechanical strength and low volume resistivity.

[0022] <Mixing process> In the mixing step, a dispersion A, which is obtained by dispersing fluororesin particles in dispersion medium A, and a dispersion B, which is obtained by dispersing carbon nanotubes in dispersion medium B, are mixed to obtain a slurry. The mixing method is not particularly limited and can be performed, for example, by mixing dispersion A and dispersion B using a known mixer or disperser. The slurry may also be obtained by mixing dispersion A and dispersion B to obtain a premixed solution, and then dispersing the obtained premixed solution. Here, the premixed solution can be obtained, for example, by mixing dispersion medium A and dispersion medium B under no pressure using a stirrer. Then, the premixed solution can be supplied to a disperser and subjected to dispersion treatment to obtain a slurry.

[0023] The mixers (agitators) and dispersers used for mixing and dispersion are not particularly limited, as long as they can mix and disperse fluororesin particles and carbon nanotubes in a dispersion medium (a mixed dispersion medium of dispersion medium A and dispersion medium B). Examples of mixers (agitators) and dispersers include high-speed agitators, inline mixers, homogenizers, ultrasonic dispersers, rotor / stator type dispersers, jet mills, and ball mills. In particular, from the viewpoint of uniformly compounding fluororesin particles and carbon nanotubes, thereby increasing conductivity without impairing the mechanical strength of the resulting composite resin material and further reducing its volume resistivity, it is preferable to perform the mixing using a stirrer equipped with a stirring section and a motor. Examples of such stirrers equipped with a stirring section and a motor include homogenizers equipped with a stirring section and a motor, and Primix's "Labo-Solution®".

[0024] <<Conditions>> The mixing (dispersion) time is not particularly limited, but is preferably between 10 minutes and 60 minutes. Furthermore, when mixing is performed using a stirrer equipped with a stirring section and motor such as a homogenizer, or a disperser with a rotor such as a rotor-stator type disperser, the rotation speed of the stirring blades or rotor is preferably between 1500 rpm and 6000 rpm.

[0025] <<Dispersion A>> Dispersion A is a dispersion obtained by dispersing fluororesin particles in dispersion medium A. Dispersion A is substantially free of carbon nanotubes. In this invention, "substantially free of carbon nanotubes" means that no carbon nanotubes other than those inevitably mixed in as impurities are added. For example, it means that the carbon nanotube content relative to the total solid content in dispersion A is less than 0.01% by mass, preferably zero. Dispersion A may be a commercially available product, or it may be obtained in the "Preparation Step for Dispersion A" described later.

[0026] The concentration of fluororesin particles in dispersion A is preferably 10% by mass or more, more preferably 20% by mass or more, and preferably 30% by mass or less.

[0027] Furthermore, it is preferable that dispersion A is substantially free of dispersants. If dispersion A is substantially free of dispersants, gas generation in the resulting composite resin material can be suppressed. Examples of dispersants include surfactants, polysaccharides, π-conjugated polymers, and polymers with ethylene chains as the main chain.

[0028] [Fluororesin particles] The fluororesin that forms the fluororesin particles is a polymer containing fluorine-containing monomer units. In this invention, "containing monomer units" means "the polymer obtained using those monomers contains repeating units derived from the monomers."

[0029] Examples of fluororesins include crystalline fluororesins such as polytetrafluoroethylene (PTFE), tetrafluoroethylene perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene hexafluoropyrpyrene copolymer (FEP), tetrafluoroethylene ethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), chlorotrifluoroethylene ethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), and polyvinyl fluoride (PVF). Preferably, the fluororesin is PTFE or PFA, with PTFE being particularly preferred. One type of fluororesin may be used alone, or two or more types may be used in combination.

[0030] The volume-average particle diameter of the fluororesin particles in dispersion A is not particularly limited, but is preferably 10 μm or more, more preferably 20 μm or more, preferably 100 μm or less, and more preferably 50 μm or less. If the volume-average particle diameter of the fluororesin particles is above the lower limit, aggregation of the fluororesin particles can be suppressed. Furthermore, if the volume-average particle diameter of the fluororesin particles is below the upper limit, the uniformity in composite formation with carbon nanotubes is increased, thereby improving the conductivity of the resulting composite resin material. In addition, clogging of the fluororesin particles can be suppressed, thereby improving the productivity of the slurry.

[0031] [Dispersion medium A] Dispersion medium A must be a non-polar solvent (substance). If dispersion medium A is a polar solvent, it will not be possible to reduce the volume resistivity of the resulting composite resin material. Examples of nonpolar solvents include hydrocarbon solvents such as benzene, toluene, cyclohexane, hexane, pentane, cyclopentane, heptane, and octane. These nonpolar solvents may be used individually or in any combination of two or more in any proportion. In particular, from the viewpoint of further increasing the mechanical strength of the resulting composite resin material while further reducing its volume resistivity, at least one of cyclohexane, hexane, pentane, cyclopentane, heptane, and octane is preferred, cyclohexane and hexane are more preferred, and cyclohexane is even more preferred.

[0032] <<Dispersion B>> Dispersion B is a dispersion obtained by dispersing carbon nanotubes in dispersion medium B. Dispersion B is substantially free of fluororesin particles. In the present invention, "substantially free of fluororesin particles" of dispersion medium B means that no fluororesin particles other than those inevitably mixed in as impurities are added, for example, that the content of fluororesin particles relative to the total solid content in dispersion B is less than 0.01% by mass, preferably zero. Dispersion B may be a commercially available product, or it may be obtained in the "Preparation Step for Dispersion B" described later.

[0033] It is preferable that dispersion B, like dispersion A, is substantially free of dispersants. If dispersion B is substantially free of dispersants, gas generation in the resulting composite resin material can be suppressed. Examples of dispersants include surfactants, polysaccharides, π-conjugated polymers, and polymers with ethylene chains as the main chain.

[0034] [Carbon nanotubes (CNT)] As carbon nanotubes, single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used, but it is preferable that the CNTs contain single-walled to five-walled carbon nanotubes, and more preferably that they contain single-walled carbon nanotubes. If the CNTs contain single-walled carbon nanotubes, the conductivity of the resulting composite resin material can be further improved.

[0035] Here, the carbon purity of the CNTs is preferably 98.0% by mass or higher, more preferably 99.0% by mass or higher, and even more preferably 99.5% by mass or higher. If the carbon purity of the CNTs is above the above lower limit, the electrical resistance of the resulting composite resin material and molded article can be further reduced.

[0036] Furthermore, the average diameter of the CNTs is preferably 1 nm or more, preferably 60 nm or less, more preferably 30 nm or less, and even more preferably 10 nm or less. If the average diameter of the CNTs is 1 nm or more, the dispersibility of the CNTs is improved, and properties such as conductivity can be stably imparted to the composite resin material and molded article. Also, if the average diameter of the CNTs is 60 nm or less, properties such as conductivity can be efficiently imparted to the composite resin material and molded article even when the amount added is small. In this invention, the "average diameter of CNTs" can be determined by measuring the diameter (outer diameter) of, for example, 20 CNTs on a transmission electron microscope (TEM) image and calculating the average value.

[0037] Furthermore, it is preferable to use CNTs in which the ratio (3σ / Av) of the standard deviation of the diameter (σ: sample standard deviation) multiplied by 3 (3σ) to the average diameter (Av) is greater than 0.20 and less than 0.60. It is more preferable to use CNTs in which 3σ / Av is greater than 0.25, and even more preferable to use CNTs in which 3σ / Av is greater than 0.40. By using CNTs in which 3σ / Av is greater than 0.20 and less than 0.60, the performance of the resulting composite resin material and molded article can be further improved. The average diameter (Av) and standard deviation (σ) of CNTs are determined by the manufacturing method and production strips of the CNTs. You can adjust it by changing the method, or combine multiple types of CNTs obtained by different manufacturing methods. You can adjust it by matching the settings.

[0038] For carbon nanotubes (CNTs), the diameter measured as described above is plotted on the x-axis and its frequency on the y-axis. When this plotted and approximated by a Gaussian matrix, the resulting matrix typically follows a normal distribution.

[0039] Furthermore, the average length of the CNTs is preferably 10 μm or more, more preferably 50 μm or more, even more preferably 80 μm or more, preferably 600 μm or less, more preferably 550 μm or less, and even more preferably 500 μm or less. If the average length is 10 μm or more, conductive paths can be formed well in the composite resin material and molded article, and dispersibility can be improved. If the average length is 600 μm or less, the conductivity of the composite resin material and molded article can be stabilized. Therefore, if the average length of the CNTs is within the above range, the surface resistivity of the molded article can be sufficiently controlled. It can be reduced to minutes. In this invention, the average length of CNTs can be determined by measuring the length of, for example, 20 CNTs on a scanning electron microscope (SEM) image and calculating the numerical average.

[0040] Furthermore, CNTs typically have an aspect ratio greater than 10. The aspect ratio of a CNT can be determined by measuring the diameter and length of 100 randomly selected CNTs using a scanning electron microscope or transmission electron microscope, and calculating the average value of the diameter-to-length ratio (length / diameter).

[0041] Furthermore, CNT has a BET specific surface area of ​​200m². 2 It is preferable that it be 1 / g or more, and 400m 2 It is more preferable that it be 600m or more per gram. 2 It is even more preferable that it be 2000m or more / g. 2 It is preferable that it be less than or equal to / g, and 1800m 2 It is more preferable that it be less than or equal to / g, and 1600m 2 It is even more preferable that the BET specific surface area of ​​the CNT is 200 m² or less. 2 If the concentration is 2000 m² or higher, the dispersibility of CNTs is improved, and properties such as conductivity of composite resin materials and molded articles can be sufficiently enhanced with a small amount of compounding. Also, if the BET specific surface area of ​​the CNTs is 2000 m² 2 If the value is less than / g, the properties of composite resin materials and molded articles, such as conductivity, can be stabilized. In this invention, "BET specific surface area" refers to the nitrogen adsorption specific surface area measured using the BET method.

[0042] Furthermore, it is preferable that the t-plot obtained from the adsorption isotherm of CNTs shows an upwardly convex shape. The "t-plot" can be obtained by converting the relative pressure to the average thickness t (nm) of the nitrogen gas adsorption layer in the adsorption isotherm of CNTs measured by the nitrogen gas adsorption method. That is, the t-plot of CNTs can be obtained by calculating the average thickness t of the nitrogen gas adsorption layer corresponding to the relative pressure from a known standard isotherm obtained by plotting the average thickness t of the nitrogen gas adsorption layer against the relative pressure P / P0 and performing the above conversion (t-plot by de Boer et al.) (The method).

[0043] In materials with pores on their surface, the growth of the nitrogen gas adsorption layer can be classified into the following processes (1) to (3). These processes (1) to (3) result in a change in the slope of the t-plot. (1) Process of forming a single-molecule adsorbed layer of nitrogen molecules on the entire surface (2) Formation of a multimolecular adsorption layer and the accompanying capillary condensation and filling process within the pores (3) Process of forming a multimolecular adsorption layer on an apparent non-porous surface where pores are filled with nitrogen

[0044] Furthermore, in the t-plot showing an upward convex shape, the plot lies on a straight line passing through the origin in the region where the average thickness t of the nitrogen gas adsorption layer is small, while as t increases, the plot shifts downward from that straight line. CNTs with this t-plot shape indicate that the ratio of the internal specific surface area to the total specific surface area of ​​the CNT is large, and that numerous openings are formed in the CNT.

[0045] Furthermore, the inflection point of the CNT t-plot is preferably within the range of 0.2 ≤ t(nm) ≤ 1.5, more preferably within the range of 0.45 ≤ t(nm) ≤ 1.5, and even more preferably within the range of 0.55 ≤ t(nm) ≤ 1.0. If the inflection point of the CNT t-plot falls within this range, the dispersibility of the CNTs can be improved, and properties such as conductivity of the composite resin material and molded article can be enhanced. Specifically, if the value of the inflection point is less than 0.2, the CNTs are more likely to aggregate and dispersibility will decrease, and if the value of the inflection point is greater than 1.5, the CNTs are more likely to entangle with each other, which may reduce dispersibility. The "position of the inflection point" is the intersection of the approximate line A from process (1) described above and the approximate line B from process (3) described above.

[0046] Furthermore, it is preferable that the ratio of the internal specific surface area S2 to the total specific surface area S1 obtained from the t-plot (S2 / S1) of the CNTs is between 0.05 and 0.30. If the S2 / S1 value of the CNTs is within this range, the dispersibility of the CNTs can be improved, and properties such as the conductivity of the composite resin material and molded article can be enhanced with a small amount of compounding. Here, the total specific surface area S1 and the internal specific surface area S2 of the CNT can be determined from its t-plot. Specifically, first, the total specific surface area S1 can be determined from the slope of the approximate line in process (1), and the external specific surface area S3 can be determined from the slope of the approximate line in process (3). Then, the internal specific surface area S2 can be calculated by subtracting the external specific surface area S3 from the total specific surface area S1.

[0047] Incidentally, the measurement of adsorption isotherms of CNTs, the creation of t-plots, and the calculation of the total specific surface area S1 and internal specific surface area S2 based on the analysis of t-plots can be performed, for example, using a commercially available measuring device called "BELSORP(registered trademark)-mini" (manufactured by Nippon Bell Co., Ltd.).

[0048] Furthermore, it is preferable that CNTs exhibit a Radial Breathing Mode (RBM) peak when evaluated using Raman spectroscopy. Note that RBMs are not present in the Raman spectra of multi-walled carbon nanotubes with three or more layers.

[0049] Furthermore, it is preferable that the ratio of the G-band peak intensity to the D-band peak intensity in the Raman spectrum (G / D ratio) of the CNT is between 0.5 and 5.0. If the G / D ratio is between 0.5 and 5.0, the performance of the manufactured composite resin material and molded article can be further improved.

[0050] Furthermore, CNTs can be manufactured using known CNT synthesis methods, such as arc discharge, laser ablation, and chemical vapor deposition (CVD), without any particular limitations. Specifically, CNTs can be efficiently manufactured, for example, by supplying raw material compounds and a carrier gas onto a substrate having a catalyst layer for carbon nanotube production on its surface, and synthesizing CNTs by chemical vapor deposition (CVD), while dramatically improving the catalytic activity of the catalyst layer by introducing a small amount of oxidizing agent (catalyst activator) into the system (super-growth method; see International Publication No. 2006 / 011655). In the following, carbon nanotubes obtained by the super-growth method may be referred to as "SGCNTs". Furthermore, the CNTs produced by the supergrowth method may consist solely of SGCNTs, or they may contain SGCNTs in addition to other carbon components, such as non-cylindrical carbon nanostructures.

[0051] [Dispersion medium B] Dispersion medium B, like dispersion medium A, must be a non-polar solvent (substance). If dispersion medium B is a polar solvent, it will not be possible to reduce the volume resistivity of the resulting composite resin material. Furthermore, the dispersion medium B can be the nonpolar solvent mentioned above as dispersion medium A. The nonpolar solvent may be used alone, or two or more may be used in any combination of proportions. In particular, from the viewpoint of further increasing the mechanical strength of the resulting composite resin material while further reducing its volume resistivity, at least one of cyclohexane, hexane, pentane, cyclopentane, heptane, and octane is preferred, cyclohexane and hexane are more preferred, and cyclohexane is even more preferred.

[0052] <<Types of dispersion medium A and dispersion medium B>> Dispersion medium A in dispersion A and dispersion medium B in dispersion B may be the same nonpolar solvent, or they may be different nonpolar solvents. From the viewpoint of suppressing changes in the state of fluororesin particles and carbon nanotubes due to mixing with different solvents and improving the conductivity of the composite resin material without impairing the mechanical strength of the resulting composite resin material, it is preferable that dispersion medium A and dispersion medium B are the same nonpolar solvent.

[0053] <<Slurry>> The slurry obtained by mixing dispersion A and dispersion B contains fluororesin particles, carbon nanotubes, dispersion medium A, and dispersion medium B. Here, the fluororesin particles in the resulting slurry may have shapes other than particle shape. Furthermore, it is preferable that the slurry is substantially free of the above-mentioned dispersants. In this invention, "substantially free of dispersants" means that no dispersants other than those inevitably mixed in as impurities are added, for example, that the content of dispersants relative to the total solid content in the slurry is less than 0.01% by mass, preferably zero.

[0054] The carbon nanotube content in the slurry is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, more preferably 0.5% by mass or less, and more preferably 0.05% by mass or less, relative to the total solid content in the slurry. If the carbon nanotube content in the slurry is above the lower limit, the conductivity of the resulting composite resin material can be increased. On the other hand, if the carbon nanotube content in the slurry is below the upper limit, conductivity can be imparted to the resulting composite resin material without impairing its mechanical strength.

[0055] <Other processes> Other steps that may be optionally included in the slurry manufacturing method of the present invention include, but are not limited to, a step of preparing dispersion A and a step of preparing dispersion B.

[0056] <<Preparation of Dispersion A>> In the preparation step for dispersion A, fluororesin particles are dispersed in dispersion medium A to prepare dispersion A. The dispersion method is not particularly limited, and known dispersants such as high-speed stirrers, inline mixers, homogenizers, ultrasonic dispersers, rotor-stator type dispersants, jet mills, and ball mills can be used. Among these, it is preferable to use a rotor-stator type dispersant to eliminate aggregates of fluororesin particles and to improve uniformity in composite formation with carbon nanotubes. An example of a commercially available rotor-stator type disperser is Primix's "Labo Solution®".

[0057] [Dispersion conditions] The conditions for dispersing fluororesin particles in dispersion medium A are not particularly limited, but the dispersion time is preferably 10 minutes or more and 60 minutes or less. Furthermore, when mixing is performed using equipment with stirring blades or rotors, such as homogenizers and rotor-stator type dispersers, the rotation speed of the stirring blades or rotor is preferably 1500 rpm or more and 6000 rpm or less.

[0058] <<Preparation of Dispersion B>> In the preparation step for dispersion B, carbon nanotubes are dispersed in dispersion medium B to prepare dispersion B. The dispersion method is not particularly limited, and known dispersants such as high-speed stirrers, inline mixers, homogenizers, ultrasonic dispersers, rotor-stator type dispersants, jet mills, and ball mills can be used. Among these, it is preferable to use an ultrasonic dispersant to improve the dispersibility of carbon nanotubes.

[0059] [Dispersion conditions] The conditions for dispersing carbon nanotubes in dispersion medium B are not particularly limited, but the dispersion time is preferably 15 minutes or more and 45 minutes or less. Furthermore, when mixing is performed using equipment with stirring blades or rotors, such as homogenizers and rotor-stator type dispersers, the rotation speed of the stirring blades or rotor is preferably 4500 rpm or more and 15000 rpm or less.

[0060] (Method of manufacturing composite resin materials) The method for producing the composite resin material of the present invention includes a step of producing a slurry using the slurry production method of the present invention described above (slurry production step) and a step of removing a dispersion medium from the slurry (dispersion medium removal step), and may optionally include other steps. The method for producing the composite resin material of the present invention uses a slurry produced by the slurry production method of the present invention described above, and therefore makes it possible to produce a composite resin material with excellent mechanical strength and low volume resistivity.

[0061] <Slurry Manufacturing Process> The slurry manufacturing process involves manufacturing the slurry using the manufacturing method of the present invention described above. The details are as described above in "Method for Manufacturing Slurry of the Present Invention," so the explanation will be omitted here.

[0062] <Dispersion medium removal process> In the dispersion medium removal process, the dispersion medium (i.e., dispersion medium A and dispersion medium B) is removed from the slurry produced in the slurry manufacturing process described above to produce a composite resin material. The method for removing the dispersion medium is not particularly limited and can include filtration, centrifugation, and drying. Among these, from the viewpoint of efficiently removing the dispersion medium while ensuring the dispersibility of carbon nanotubes, it is preferable to use a method other than filtration, and it is preferable to directly dry the slurry. Here, known drying methods such as spray drying, vacuum drying, and drying by circulating inert gas can be used as drying methods.

[0063] <Other processes> Other steps that may be included in the method for producing the composite resin material of the present invention include, for example, a grinding step. In the grinding process, the composite resin material obtained in the dispersion medium removal process is ground. The grinding method is not particularly limited, and any grinding method can be used. As for the grinding equipment, a crushing, granulating, and sizing machine capable of crushing, sizing, and granulating can be used, such as a mill mixer, quick mill, Wonder Crusher, or Henschel mixer. The grinding process can be carried out under normal temperature and pressure conditions without any particular limitations.

[0064] (Composite resin material) The composite resin material of the present invention is manufactured by the method for manufacturing the composite resin material of the present invention described above, and is composed of fluororesin particles and carbon nanotubes. Furthermore, from the viewpoint of suppressing gas generation and the like, it is preferable that the composite resin material of the present invention substantially does not contain the above-mentioned dispersant. In this invention, "substantially free of dispersant" means that the composite resin material does not contain any dispersant other than those that are inevitably mixed in as impurities, for example, that the content of dispersant relative to the total mass of the composite resin material is less than 0.01% by mass, preferably zero.

[0065] <Impossible / Impossible circumstances> Here, as described above, the composite resin material of the present invention is obtained by mixing a dispersion liquid obtained by dispersing fluororesin particles in a nonpolar solvent as a dispersion medium with a dispersion liquid obtained by dispersing carbon nanotubes in a nonpolar solvent as a dispersion medium, and then removing the dispersion medium from the resulting slurry. In contrast, in conventional methods such as those described in Patent Document 1 above, when obtaining a slurry containing carbon nanotubes and fluororesin particles, the fluororesin particles and carbon nanotubes are mixed and dispersed together with cyclohexane (a nonpolar solvent) (see Comparative Examples 6 and 7 of this application). As shown in the "Examples" section below, in the examples of this application, it is possible to achieve both a low volume resistivity and excellent mechanical strength (tensile strength, elongation) in the composite resin material at a higher level than in Comparative Examples 6 and 7. Thus, there are significant differences in the properties (volume resistivity, mechanical strength) of the resulting composite resin material depending on whether the slurry is obtained by dispersing fluororesin particles and carbon nanotubes together or by mixing two dispersions in which they are dispersed separately. This indicates that the properties of the composite resin material strongly depend on the dispersion method of the fluororesin particles and carbon nanotubes. However, in composite resin materials, fluororesin particles and carbon nanotubes are usually dispersed in a highly complex manner. Current analytical methods (electron microscopy, XRD, etc.) make it difficult to clearly identify the internal structure of the composite resin material or the differences in the dispersion state of fluororesin particles and carbon nanotubes. Furthermore, it is difficult to explain these differences solely by composition or simple component ratios. Therefore, it is practically impossible to analyze the structure and properties that contribute to the effects of the present invention. Even if it were possible, identifying these structures and properties would require an excessively large economic expenditure and time. Therefore, at the time of filing this application, it was impossible or impractical to directly identify the composite resin material of the present invention by its structure or properties; in other words, there was an "impossible or impractical circumstance." Accordingly, it is appropriate to define the composite resin material of the present invention as "manufactured by a method for manufacturing composite resin materials."

[0066] <Content Ratio of Each Component> The content ratio of each component in the obtained composite resin material may be the same as the ratio of each solid content contained in the slurry described above. Specifically, the content ratio of carbon nanotubes in the composite resin material is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, preferably 0.5 mass% or less, and more preferably 0.05 mass% or less. In addition, the content ratio of fluororesin particles in the composite resin material is preferably 99.50 mass% or more, more preferably 99.95 mass% or more, preferably 99.99 mass% or less, and more preferably 99.98 mass% or less.

[0067] <Volume Resistivity> The composite resin material of the present invention has a volume resistivity of 1×10 8 Ω·cm or less, more preferably 1×10 7 Ω·cm or less, and even more preferably 1×10 4 Ω·cm or less. When the volume resistivity is not more than the above upper limit, the antistatic performance is excellent. Therefore, the composite resin material is useful as a material for producing, for example, semiconductor manufacturing apparatus components, chemical liquid tanks, wafer cleaning containers, cleaning nozzles, antistatic sheets, trays for integrated circuits, wafer carriers, chemical liquid hoses, pipe joints, diaphragms, sealing materials and the like. In the present invention, the volume resistivity can be measured by the method described in the Examples.

[0068] <Tensile Strength> The composite resin material of the present invention preferably has a tensile strength of 25 MPa or more when formed into a molded body, more preferably 30 MPa or more. When the tensile strength is at least the above lower limit, the mechanical strength is excellent. In the present invention, the tensile strength can be measured by the method described in the Examples.

[0069] <Elongation at Break> The composite resin material of the present invention preferably has a fracture elongation of 200% or more when molded, and more preferably 300% or more. If the fracture elongation is above the lower limit, it exhibits excellent mechanical strength. In this invention, the elongation at break can be measured by the method described in the examples.

[0070] (Molded body) The molded article of the present invention is obtained by molding the composite resin material of the present invention as described above. The molded article of the present invention preferably has at least one, preferably all, of the volume resistivity, tensile strength, and elongation at break as described in the "Composite Resin Material" section.

[0071] <Manufacturing method> The method for manufacturing a molded article of the present invention includes a step of molding a composite resin material manufactured using the method for manufacturing a composite resin material of the present invention described above. The molding of composite resin materials is not particularly limited and can be carried out using a molding machine, such as an extruder, injection molding machine, compressor, or roll machine, depending on the desired shape of the molded product. [Examples]

[0072] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. In the examples and comparative examples, various measurements and evaluations were performed using the methods described below.

[0073] <Volume-average particle size (D50)> For the fluororesin particle-containing dispersions prepared in the examples and comparative examples, the particle size distribution of the fluororesin particles was measured using a laser diffraction particle size analyzer (manufactured by HORIBA). The median particle size in volume fraction was obtained from the resulting particle size distribution and defined as the volume-average particle size (D50). <Volume resistivity> The surface of the molded bodies prepared in the examples and comparative examples was polished with waterproof abrasive paper (3000 grit), and then the volume resistivity (Ω·cm) of the molded bodies was measured. Here, the low volume resistivity (1 × 10⁻⁶) 8High volume resistivity (1 × 10⁻¹⁰) is measured using a resistivity meter (Loresta, manufactured by Mitsubishi Chemical Analytec, product name "MCP-T610", probe LSP) 8 Resistivity values ​​(Ω·cm or greater) were measured using a resistivity meter, Hi-Resta (manufactured by Mitsubishi Chemical Analytec Co., Ltd., product name "MCP-HT800", probe URSS). A smaller volume resistivity value indicates superior conductivity and high antistatic performance. <Tensile Test> Test specimens specified in JIS K7137-2 were formed from the molded bodies produced in the examples and comparative examples, and tensile tests were performed using a tensile testing machine (manufactured by Toyo Seiki Co., Ltd.) to obtain the tensile strength and elongation at fracture.

[0074] (Example 1) <Slurry Manufacturing> [Fluororesin particle dispersion process] 99.95 g of fluoropolymer particles (product name "Fluon PTFE G163", manufactured by AGC, polytetrafluoroethylene) were added to 350 g of cyclohexane as a nonpolar solvent (dispersion medium), and the mixture was mixed at 12,000 rpm for 15 minutes using a disperser (product name "Labo-Solution®", manufactured by Primix) to prepare dispersion A. The volume-average particle size of the fluoropolymer particles was then measured using dispersion A. The results are shown in Table 1. [Carbon nanotube dispersion process] Dispersion B was prepared by dispersing a mixture of 0.05 g of single-walled carbon nanotubes (product name "ZEONANO SG101", manufactured by Zeon Corporation) and 50 g of cyclohexane as a nonpolar solvent (dispersion medium) using a rotating ultrasonic nanodispersor (manufactured by Thinky Corporation) at an output of 150 W for 30 minutes. [Mixing process] Dispersion A and dispersion B were mixed, and the resulting mixture was dispersed at 2500 rpm for 15 minutes using a disperser (manufactured by Primix Corporation) to prepare a slurry containing fluororesin particles and carbon nanotubes.

[0075] <Manufacturing of composite resin materials> [Drying process] The slurry obtained in the above mixing process was poured into a tray, dried in a fume hood to remove the dispersion medium, and then vacuum dried at 125°C for 2 hours in a rectangular vacuum dryer (manufactured by Yamato Scientific Co., Ltd.) to obtain a composite resin material containing fluororesin particles and carbon nanotubes.

[0076] <Manufacturing of molded products> The composite resin material obtained through the above drying process was passed through a sieve (mesh opening 1.4 mm), placed in a mold, and pre-molded using a compression molding machine (Dumbbell Co., Ltd.) at room temperature, a pressure of 9 MPa, and a pressure holding time of 5 minutes to obtain a sheet-like pre-molded body measuring 130 mm wide x 80 mm thick and 2 mm thick. After demolding the pre-molded product, the molded body was obtained by firing it in an inert oven (JTEKT Thermo Systems Co., Ltd.) at 370°C for 6 hours. The volume resistivity, tensile strength, and elongation at break of the obtained molded body were measured. The results are shown in Table 1.

[0077] (Example 2) In Example 1, a slurry, composite resin material, and molded article were manufactured in the same manner as in Example 1, except that hexane was used instead of cyclohexane as the nonpolar solvent in the [fluororesin particle dispersion step], and various measurements were performed. The results are shown in Table 1.

[0078] (Example 3) In the [fluororesin particle dispersion step] of Example 1, "New Polyflon PTFE M-112 (Daikin Industries, Ltd., polytetrafluoroethylene)" was used instead of "Fluon PTFE G163" (AGC Corporation) as the fluororesin particles. Otherwise, the slurry, composite resin material, and molded article were manufactured in the same manner as in Example 1, and various measurements were performed. The results are shown in Table 1.

[0079] (Example 4) In Example 1, a slurry, composite resin material, and molded article were manufactured in the same manner as in Example 1, except that "Fluon PTFE G190" (manufactured by AGC Inc.) was used instead of "Fluon PTFE G163" (manufactured by AGC Inc.) as the fluororesin particles in the [fluororesin particle dispersion step] of Example 1. Various measurements were then performed. The results are shown in Table 1.

[0080] (Example 5) In Example 4, a slurry, composite resin material, and molded article were produced in the same manner as in Example 4, except that hexane was used instead of cyclohexane as the nonpolar solvent in the [fluororesin particle dispersion step], and various measurements were performed. The results are shown in Table 1.

[0081] (Comparative Example 1) In Example 1, a slurry, composite resin material, and molded article were manufactured in the same manner as in Example 1, except that methyl ethyl ketone (MEK) was used as a polar solvent instead of cyclohexane as a nonpolar solvent in the [fluororesin particle dispersion step], and various measurements were performed. The results are shown in Table 1.

[0082] (Comparative Example 2) In Example 1, a slurry, composite resin material, and molded article were manufactured in the same manner as in Example 1, except that isopropanol (IPA) was used as a polar solvent instead of cyclohexane as a nonpolar solvent in the [fluororesin particle dispersion step], and various measurements were performed. The results are shown in Table 1.

[0083] (Comparative Example 3) In Example 1, slurry, composite resin material, and molded articles were manufactured in the same manner as in Example 1, except that isopropanol (IPA) was used as a polar solvent instead of cyclohexane as a nonpolar solvent in the [fluororesin particle dispersion step] and [carbon nanotube dispersion step]. Various measurements were then performed. The results are shown in Table 1.

[0084] (Comparative Example 4) In Example 3, a slurry, composite resin material, and molded article were produced in the same manner as in Example 3, except that methyl ethyl ketone (MEK) was used as a polar solvent instead of cyclohexane as a nonpolar solvent in the [fluororesin particle dispersion step], and various measurements were performed. The results are shown in Table 1.

[0085] (Comparative Example 5) In Example 4, a slurry, composite resin material, and molded article were manufactured in the same manner as in Example 4, except that methyl ethyl ketone (MEK) was used as a polar solvent instead of cyclohexane as a nonpolar solvent in the [fluororesin particle dispersion step], and various measurements were performed. The results are shown in Table 1.

[0086] (Comparative Example 6) In Example 1, a slurry, composite resin material, and molded article were manufactured in the same manner as in Example 1, except that the slurry was prepared as described below, and various measurements were performed. The results are shown in Table 2. <Slurry Manufacturing> 99.95 g of fluororesin particles (product name "New Polyflon PTFE M-112" manufactured by Daikin Industries, Ltd.) and 0.05 g of single-walled carbon nanotubes (product name "ZEONANO SG101" manufactured by Nippon Zeon Co., Ltd.) were added to 350 g of cyclohexane as a nonpolar solvent (dispersion medium). The mixture was then stirred for 30 minutes at 20°C and a rotation speed of 6000 rpm using an in-line mixer called Cavitron (manufactured by Taiheiyo Kiko Co., Ltd., product name "CD1000", rotor / stator: slit type, slit width 0.4 mm) to obtain a slurry containing fluororesin particles and carbon nanotubes.

[0087] (Comparative Example 7) In Comparative Example 6, slurry, composite resin material, and molded articles were manufactured in the same manner as in Comparative Example 6, except that "Labo-Solution®" was used as the dispersant instead of "Cavitron". Various measurements and evaluations were then performed. The results are shown in Table 2. [Table 1] [Table 2]

[0088] As shown in Tables 1 and 2, in Examples 1 to 5, a slurry was obtained by mixing dispersion A, which is obtained by dispersing fluororesin particles in dispersion medium A, with dispersion B, which is obtained by dispersing carbon nanotubes in dispersion medium B, and non-polar solvents were used as dispersion mediums A and B. This shows that a composite resin material with excellent mechanical strength and low volume resistivity can be obtained. [Industrial applicability]

[0089] According to the present invention, it is possible to provide a method for producing a slurry that can obtain a composite resin material with excellent mechanical strength and low volume resistivity. Furthermore, according to the present invention, it is possible to provide a method for producing a composite resin material that has excellent mechanical strength and low volume resistivity. Furthermore, according to the present invention, it is possible to provide a composite resin material that has excellent mechanical strength and low volume resistivity.

Claims

1. The process includes a step of mixing a dispersion A, which is obtained by dispersing fluororesin particles in a dispersion medium A, with a dispersion B, which is obtained by dispersing carbon nanotubes in a dispersion medium B, to obtain a slurry. A method for producing a slurry, wherein the dispersion medium A and the dispersion medium B are nonpolar solvents.

2. A method for producing a slurry according to claim 1, further comprising the steps of: dispersing the fluororesin particles in the dispersion medium A to prepare the dispersion A; and dispersing the carbon nanotubes in the dispersion medium B to prepare the dispersion B.

3. The method for producing a slurry according to claim 2, wherein in the step of preparing the dispersion A, the fluororesin particles are dispersed using a rotor-stator type disperser.

4. The method for producing a slurry according to claim 1, wherein the dispersion medium A and the dispersion medium B are the same nonpolar solvent.

5. The method for producing a slurry according to claim 1, wherein the dispersion A and the dispersion B each substantially contain no dispersant.

6. The method for producing a slurry according to claim 1, wherein the volume-average particle diameter of the fluororesin particles in the dispersion A is 100 μm or less.

7. The method for producing a slurry according to claim 1, wherein the content of the carbon nanotubes in the slurry is 0.01% by mass or more and 0.5% by mass or less with respect to the total solid content in the slurry.

8. The method for producing a slurry according to claim 1, wherein the dispersion A and the dispersion B are mixed using a stirrer equipped with a stirring unit and a motor.

9. The method for producing a slurry according to claim 1, wherein the dispersion medium A and the dispersion medium B are each at least one selected from the group consisting of cyclohexane, hexane, pentane, cyclopentane, heptane, and octane.

10. A step of manufacturing a slurry using a slurry manufacturing method according to any one of claims 1 to 9, A method for producing a composite resin material, comprising the step of removing a dispersion medium from the slurry.

11. A composite resin material manufactured by the method for manufacturing a composite resin material described in claim 10.

Citation Information

Patent Citations

  • Method for producing slurry and method for producing composite resin material

    JP2017031323A